Emotional labor and burnout among Turkish primary school teachers - Akin, Ugur; Aydin, Inayet; Erdogan, Cetin; Demirkasimoglu, Nihan (SPRINGER, 2014)
Emotions play a critical role in teaching, especially in primary schools. Teachers have to manage their feelings in order to sustain a positive classroom climate. Managing feelings as a requirement of work is called emotional labor, which is a relatively new area of research in teaching. The main aim of this research was to investigate the type of emotional labor strategies Turkish primary school teachers often use and whether emotional labor is a predictor of burnout for primary teachers in a Turkish context. Also, the authors explore if there is a significant variation in emotional labor in terms of gender and school type (public/private). A survey was conducted with the participation of 370 primary school teachers from Ankara, Turkey. Results indicated that Turkish primary school teachers mostly engage in genuine emotions in their relationships with students. Female teachers use deep and surface acting strategies more often than males. Also, private school teachers were found to use deep acting strategies and display genuine emotions more often than public school teachers. Finally, it was found that emotional labor is a significant predictor of burnout among Turkish primary school teachers.
Keywords: Managing feelings; Emotional labor; Burnout; Primary school teachers; WORK; CONSEQUENCES; SATISFACTION; ANTECEDENTS; VALIDATION; EXHAUSTION; DISSONANCE; GENDER; Education & Educational Research